Development and validation of a sustainable diet index among Malaysian adults : protocol - Nur Fadzlina Zulkefli,; Foong, Ming Moy (Penerbit Universiti Kebangsaan Malaysia, 2021)
Adopting a sustainable diet is an alternative to address the pandemics of obesity, undernutrition and climate change that are threatening human health. Sustainable diet considers the health aspect as well as the environmental impact of diets. There is a scarcity of research on sustainable diet and lack validated tools for its measurement. This article aimed to describe the protocol on the development and validation of a Sustainable Diet Index (SDI) among Malaysian adults. A Sustainable Diet Index (SDI) was developed based on previous studies and available dietary guidelines on sustainable diet. Five indicators (rice, animal-based food, plant-based food, food waste and packaging) were included in the SDI. The index will be validated among Malaysian adults using mobile food record as the dietary assessment tool. The index has the potential to measure the level of healthy and sustainable diet behaviour of an individual. The use of mobile food record provides images of each eating occasion for the evaluation of serving size and the information on waste management. Health and environmental impacts from the diet can be evaluated through the integration of all indicators in the SDI. The index developed is novel and expected to provide a feasible measurement to assess the level of sustainable diet of an individual.